2010
DOI: 10.1007/s10728-010-0152-x
|View full text |Cite
|
Sign up to set email alerts
|

Can Questions of the Privatization and Corporatization, and the Autonomy and Accountability of Public Hospitals, Ever be Resolved?

Abstract: Although there is a long-standing international debate concerning the privatization and corporatization of health services, there has been relatively little systematic analysis of the ways these types of reform manifest. We examine the impact of privatization and corporatization on public hospitals, and in particular on hospitals' autonomy and accountability, with two aims: to uncover the key themes in the literature, and to consider implementation issues. The review of 2,319 articles was conducted using conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…As healthcare in European countries in the recent years has become to some extent more private, studies have been carried out to evaluate the effects [ 47 ]. However, a recent review stated that the evidence for recurring privatisation questions is weak and mixed [ 48 ]. The public-private mix in Swedish primary healthcare has changed substantially with consequences difficult to predict while the lack of data and neglect of research in this field have hindered informed policy-making [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As healthcare in European countries in the recent years has become to some extent more private, studies have been carried out to evaluate the effects [ 47 ]. However, a recent review stated that the evidence for recurring privatisation questions is weak and mixed [ 48 ]. The public-private mix in Swedish primary healthcare has changed substantially with consequences difficult to predict while the lack of data and neglect of research in this field have hindered informed policy-making [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that corporate standardisation of issues such as clinical guidelines can help to secure improvement, and that common facility standardisation can also be beneficial, though standardising administration alone is not sufficient to increase care quality. 26,27 Having a large number of practices within the organisation enabled Primer to develop common policies that could be widely implemented. Like other larger firms, 28 Primer appeared able to cope better with standardisation and regulation than small enterprises, the company having the advantages of added managerial capacity with central leadership and management by concentrating resources in its head office, and relieving front-line GPs of administrative duties.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the outcomes of hospital autonomisation are often lower than expected, and the evidence is hard to find due to the lack of well‐designed scientific evaluation (Braithwaite, Travaglia, & Corbett, ). For example, in China, research on the effect of autonomisation is almost non‐existent, whereas in the United Kingdom, the evidence existed is contradictory (Ibid).…”
Section: Hospital Autonomisationmentioning
confidence: 99%